Redesigning of Mobile Content to Enhance Learning Activities Preparation by Preschool Experts - Irwan Mahazir, Ismail; Sanmugam, Mageswaran; Hadi, Hassan; Mohamad Basri, Nadzer; Azwin Arif, Abdul Rahim; Nor Yazi, Khamis (International Association of Online Engineering, 2023)
Mobile content provision at the preschool stage has grown after the post-pandemic Covid-19. Preschool teachers face varying degrees of mobile technology literacy to prepare learning activities that enhance children’s understanding and acquisition of knowledge and skills. Nevertheless, these teachers have minimal exposure and input to mobile content elements that can enhance learning. This study aims to redesign the mobile content model by redefining the required elements to improve learning activities preparation for preschoolers’ basic problem-solving skills in mathematics. This case study involves seven preschool experts whose data was collected using the Nominal Group Technique approach. Then, Interpretive Structural Modelling was applied to develop the model through a voting process. The technique was used to rank the data from the experts before running the voting session. The findings revealed eleven principal elements for the mobile content model that can be divided into three content execution streams. The results offer several implications and benefits to the mobile learning arena, particularly in early childhood education, due to its potential to enhance engagement, interaction, and personalized learning experiences for young learners. These outcomes provide insights into the best practices, strategies, and pedagogical approaches that can optimize the use of mobile devices in early childhood education, hence, promoting effective learning outcomes. © 2023 by the authors of this article.